Acute liver failure - Bansal, Sanjay (Indian J Pediatr, 2006)
Acute liver failure in children is a rare but potentially fatal disease. Causes of ALF in neonatal period are different from those in early or late childhood. Despite the improvement in the paediatric intensive care, liver transplantation remains the only effective treatment. Use of newer treatment modalities (liver assist devices and hepatocyte transplantation) is still in experimental phase. Management requires early recognition, prompt diagnosis of treatable condition, supportive therapy and prevention of complications hence these children should ideally be treated in a specialist unit.